Pengaruh Pemberian Pupuk Kandang Sapi Terhadap Serapan Hara N, P, K Tanaman Cabai Merah (Capsicum annum. L) di Tanah Alluvial - Saputri, Ella; Indrawati, Urai Suci Yulies; Junaidi, Junaidi (Fakultas Pertanian Universitas Tanjungpura, 2025)
Chili pepper is included in the Family Eggplant (Solanaceae) and is a plant that is easily planted in the lowlands or in the highlands. There is considerable potential for developing vegetables, especially red chili plants, on alluvial soils in West Kalimantan. For this reason, it's necessary to increase red chili plant production by improving soil nutrient availability with cow manure. This study aims to analyze the effect of applying cow manure at different doses on the absorption of N, P, and K and the yield of red chili plants (Capsicum annum L). This research was conducted on the Pontianak Kota sub-district, and an Analysis of Soil Chemical Properties was carried out in the Laboratory of Chemistry and Soil Fertility. This study uses a non-factorial complete random design (RAL) with 5 treatments, each repeated 5 times, yielding 25 experimental units. Treatment doses P0 (without treatment), P1 30 tons/ha (157 g/ g/polybag), P2 60 tons/ha (315 g/ g/polybag), P3 90 tons/ha (473 g/ g/polybag), and P4 120 tons/ha (631 g/ g/polybag). The results of the effect of giving the best cow manure were found in the treatment of P3 90 tons/ha (473 g/ g/polybag), which could increase the dry weight of the plant by 10.29%, N 21,42%, absorption, P 16,66%, and K 17,61%.) g/polybag), P3 90 ton/ha (473 g/polybag), dan P4 120 ton/ha (631 g/polybag). Hasil penelitian pengaruh pemberian pupuk kandang sapi terbaik terdapat pada perlakuan P3 90 ton/ha (473 g/polybag) yang mampu meningkatkan berat kering tanaman sebesar 10,29%, N 21,42%, serapan, P 16,66%, dan K 17,61%.